Application of hydroponic systems for the treatment of source-separated human urine - Yang, Linyan (2015)
Hydroponic systems are widely used for the treatment of nutrient rich wastewaters. In this study, a hydroponic system was applied as the final treatment stage of source-separated human urine after urea hydrolysis, induced-struvite precipitation and ammonia stripping in tropical conditions (Singapore). The results showed that water spinach grew efficiently in the pretreated urine with 1:50 dilution ratio at the growth rate 0.68 cm/d, leaf number 2.27 pieces/d, shoot dry mass 0.33 g, water content 93.86%, and nitrogen and potassium conversion rate 0.46 and 0.51 mg/mg, respectively. This hydroponic system removed 58–66% chemical oxygen demand (COD), 41–49% total nitrogen (TN) and up to 47% total suspended solid (TSS), indicating sufficient urine stream polishing. Nitrification was observed when COD reduced by 60%, possibly because of oxygen competition between nitrobacteria for nitrification and microbes for COD degradation. The kinetic study revealed that zero-order model provided best fitting for COD and ammonia-nitrogen (NH4+-N) removal, while second-order model was more suitable for TN removal.